2018 IEEE Working Conference on Software Visualization (VISSOFT) 2018
DOI: 10.1109/vissoft.2018.00021
|View full text |Cite
|
Sign up to set email alerts
|

Scoped: Evaluating A Composite Visualisation of the Scope Chain Hierarchy Within Source Code

Abstract: This paper presents two studies that evaluate the effectiveness of a software visualisation tool which uses a composite visualisation to encode the scope chain and information related to the scope chain within source code. The first study evaluates the effectiveness of adding the composite visualisation to a source code editor to help programmers understand scope relationships within source code. The second study evaluates the effectiveness of each individual component within the composite visualisation. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Interesting questions in the context of scope issues include where (in which scope) was a specific variable defined and where in the code can a global variable be changed. Bacher et al [11] conducted an analysis of the 50 most popular stack overflow questions in the context of scope understanding issues within source code. The authors found that programmers have difficultly understanding issues regarding the declaration, accessibility, and state of an identifier (variable, function, or parameter).…”
Section: Source Code Understandingmentioning
confidence: 99%
See 1 more Smart Citation
“…Interesting questions in the context of scope issues include where (in which scope) was a specific variable defined and where in the code can a global variable be changed. Bacher et al [11] conducted an analysis of the 50 most popular stack overflow questions in the context of scope understanding issues within source code. The authors found that programmers have difficultly understanding issues regarding the declaration, accessibility, and state of an identifier (variable, function, or parameter).…”
Section: Source Code Understandingmentioning
confidence: 99%
“…As many source code maintenance and comprehension issues are due to the poor understanding of scope [11], we believe that adding a layer to the code mini-map visualisation which encodes information related to the scope chain hierarchy within a source code document can facilitate source code understanding. Hence, we will be focusing on tasks that evaluate a programmer's ability to answer questions such as in which scope is an identifier declared, and can an identifier be accessed from a specific line of code?…”
Section: Source Code Understandingmentioning
confidence: 99%
“…For programmers, one of the most challenging and time-consuming tasks is comprehending source code (Steinmacher et al 2016;Al-Saiyd 2017;Bacher et al 2017;Khomokhoana and Nel 2019). Current solutions to address these problems include visualizations to display code, enhanced syntax highlighting, and code comprehension through games (Merino et al 2018;Oberhauser and Lecon 2017;Wiese et al 2019).…”
Section: Introductionmentioning
confidence: 99%